Latihan Mendalami Kitab Suci Untuk Persekutuan Doa Karismatik Katolik Paroki Liquica, Timor Leste - Siprianus S. Senda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Scriptures is a way of life for human beings who believe in Catholicism. The holy Bible contains the word of God which is an inspiration for human beings of faith to manage life properly and correctly. Therefore, it is very important to pronounce the scriptures for the faithful as expected by the Second Vatican Council (Dei Verbum 25). Responding to the wishes of the Council, the Bible Study for the Catholic Charismatic Prayer Fellowship of the Liquica Parish, Timor Leste, was carried out as part of community service. The Catholic Charismatic Prayer Fellowship consists of Catholic faithful who need guidance in reading and studying the holy scriptures. The method used is an explanation of the scriptures and techniques for reading and studying the texts of the scriptures in a simple way. As a result, the participants gained a global understanding of the scriptures and simple techniques for reading and studying the scriptures.